Identification of a novel, recurrent MBTD1‐CXorf67 fusion in low‐grade endometrial stromal sarcoma. Issue 5 (4th September 2013) - Dewaele, Barbara; Przybyl, Joanna; Quattrone, Anna; Finalet Ferreiro, Julio; Vanspauwen, Vanessa; Geerdens, Ellen; Gianfelici, Valentina; Kalender, Zeynep; Wozniak, Agnieszka; Moerman, Philippe; Sciot, Raf; Croce, Sabrina; et al.
<x xml:space="preserve">Abstract</x> Endometrial stromal sarcomas (ESSs) are a genetically heterogeneous group of rare uterine neoplasms that are commonly driven by recurrent gene rearrangements. In conventional low‐grade ESS, JAZF1‐SUZ12, PHF1‐JAZF1, EPC1‐PHF1 and MEAF6‐PHF1, and recently described ZC3H7‐BCOR chimeric fusions have been reported in > 50% of cases. Conversely, oncogenic t(10;17)(q22;p13) translocation yields YWHAE‐FAM22A/B chimeric proteins that are associated with histologically high‐grade and clinically more aggressive ESS. Integrating whole‐transcriptome paired‐end RNA sequencing with fluorescence in situ hybridization (FISH) and banding cytogenetics, we identified MBTD1 (malignant brain tumor domain‐containing 1) and CXorf67 (chromosome X open reading frame 67) as the genes involved in the novel reciprocal t(X;17)(p11.2;q21.33) translocation in two independent low‐grade ESS of classical histology. The presence of the MBTD1‐CXorf67 fusion transcript was validated in both cases using reverse‐transcription polymerase chain reaction followed by Sanger sequencing. A specific FISH assay was developed to detect the novel t(X;17) translocation in formalin‐fixed paraffin‐embedded material, and resulted in identification of an additional low‐grade ESS case positive for the MBTD1‐CXorf67 fusion among 25 uterine stromal tumors [14 ESS and 11 undifferentiated endometrial sarcomas (UESs)] that were negative for JAZF1 and YWHAE rearrangements. Gene expression profiles of seven ESS (including three with YWHAE and two with JAZF1 rearrangements) and four UES without specific chromosomal aberrations indicated clustering of tumors with MBTD1‐CXorf67 fusion together with low‐grade JAZF1‐associated ESS. The chimeric MBTD1‐CXorf67 fusion identifies yet another cytogenetically distinct subgroup of low‐grade ESS and offers the opportunity to shed light on the functions of two poorly characterized genes.